The effectiveness and the consequences of the use of recombinant bovine somatotropin - BROZOS (Χ. Ν. ΜΠΡΟΖΟΣ) C. N.; SARATSIS (Φ. ΣΑΡΑΤΣΗΣ) Ph. (Journal of the Hellenic Veterinary Medical Society, 2018)
Growth hormone (also known as somatotropin) plays a dominant role on the development and metabolism of mammalians. Since the early 1950’s it has been known that the administration of somatotropin in milk productive animals leads to an increase in milk yield. Nevertheless, its high cost of manufacture didn’t allow the massive application, until recently. Genetic engineering achieved the production of recombinant bovine somatotropin (bST) and therefore has permitted the commercial use. Numerous of publications confirm a 10-30% increase in dairy cattle milk yield after bST administration. The mechanism of action of bST involves a series of orchestrated changes in the metabolism of body tissues so that more nutrients can be used for milk synthesis. Long-term bST administration has no effects on animal welfare. The reproductive system od bST treated cows seems to be prone to disorders. These disorders have been found to be insignificant. Advanced quality of management is necessary to accomplish maximum bST response in dairy cattle. BST is homologous to that of sheep and therefore can be successfully used in ewes as well. Due to the large number of dairy ewes in Greece, this is of great importance to Greek animal industry.